Effect of emoji prime on the understanding of emotional words – evidence from ERPs. Issue 6 (26th April 2022) - Yang, Jiayi; Yang, Yingxi; Xiu, Lichao; Yu, Guoming
ABSTRACT: Emojis play an increasingly important role as nonverbal symbols in online communication, and this study investigates their effect on the processing of subsequent words. We suppose that emojis, as an aid to emotional expression and semantic comprehension, prime the cognitive processing of the textual stimuli that follow. An affective priming experiment using ERPs was conducted, in which Semantic Relationship between the emoji and the word (Congruent, Incongruent, Non-related) was manipulated to assess their impact in an affective word categorization task. Behavioral results revealed no significant difference, while electrophysiological data showed otherwise. N1 component elicited by semantically congruent and incongruent emoji-word pairs showed greater amplitudes than those by non-related pairs. N400 elicited by incongruent pairs showed greater amplitudes than the N400 by congruent pairs. These data indicate that while emojis do not influence the outcomes of linguistic processing, emoji primes enhance attentional level, and semantically congruent contents demand fewer cognitive resources and facilitate better processing in comparison to incongruent ones. The findings point to emojis' role not only as affective primes, but also as paralanguage that is semantically processed. Implications for computer-mediated communication are discussed.